Cellular and proteomic differences associated with lithium response in olfactory neuroepithelium cells of bipolar disorder patients - Hidalgo-Figueroa, Maria; Delgado-Sequera, Alejandra; Pérez-Ramos, Anaid; Durán-Ruiz, MªCarmen; Romero-Lopez-Alberca, Cristina; Pérez-Revuelta, Jose I.; Marquez-Estefenn, Ingrid; García-Mompó, Clara; Moreno, Jose Ma Villagrán; Berrocoso, Esther (Molecular medicine (Cambridge, Mass.), 2025)
Background Lithium is a first-line treatment for bipolar disorder (BD), but only 30% of patients respond satisfactorily to monotherapy, and the biological basis for this variability remains unclear. This study aimed to identify potential biomarkers and therapeutic targets by analyzing olfactory neuroepithelium (ONE) cells from BD lithium non-responders (BDNR), responders (BDR), and control subjects. Methods Immunofluorescence and proteomic analyses of ONE cells were conducted. Blood samples were examined to improve accessibility for clinical applications. Results Immunofluorescence and proteomic analyses of ONE cells revealed that BDNR cells exhibited impaired adhesion capacity, which was restored by lithium treatment in vitro. However, BDNR cells also showed significant alterations in cell morphology and cytoskeletal organization that were unaffected by lithium. Proteomic analysis identified significant changes in pathways associated with “cell morphology,” with CDN2A highlighted as a key protein. In BDR cells, lithium treatment restored adhesion capacity but failed to reverse migration deficits. Proteomic analysis of BDR ONE cells identified differentially expressed proteins linked to neurotransmitter release, synaptic function, and mitochondrial activity, many of which were significantly modulated by lithium. Additionally, peripheral blood mononuclear cells from BDR patients displayed lower levels of RHOC protein, mirroring reductions seen in ONE BDR cells treated with lithium. Conclusions This study underscores cellular and proteomic differences between BDNR and BDR cells, with lithium exerting pronounced effects on BDR cells while having limited impact on BDNR cells. These findings advance our understanding of lithium responsiveness in BD and point to potential biomarkers and therapeutic targets for personalized treatment approaches.